Slight thermal stress exerts genetic diversity selection at coral (Acropora digitifera) larval stages - Cristiana Manullang; Nozomi Hanahara; Ariyo Imanuel Tarigan; Yuko Abe; Mao Furukawa; Masaya Morita (BMC Genomics)
Abstract Background Rising seawater temperatures increasingly threaten coral reefs. The ability of coral larvae to withstand heat is crucial for maintaining reef ecosystems. Although several studies have investigated coral larvae’s genetic responses to thermal stress, most relied on pooled sample sequencing, which provides population-level insights but may mask individual genotype variability. This study uses individual larval sequencing to investigate genotype-specific responses to heat stress and the selective pressures shaping their genomes, offering finer resolution and deeper insights. Results This study investigates the larval response to heat stress before acquiring symbiotic algae, aiming to elucidate the relationship between coral genetic diversity and heat stress. Larvae sourced from eight Acropora digitifera colonies were subjected to ambient temperature (28 °C) and heat conditions (31 °C). The impact of heat stress on larval genetic diversity was assessed through sequencing. While overall genetic diversity, represented by π, did not significantly differ between the control and heat-exposed groups, Tajima’s D differed, indicating different selective pressures in each group. The genomic regions under higher and lower Tajima’s D were not broadly shared among control and head conditions, implying that selective pressures operated in distinctive manners. Many larval protein-coding sequences were identified in this genomic region, and the codon evolution of many of these genes showed signs of positive selection. These results highlight the complex selective pressures on coral larvae under different temperatures. The genes showing signs of positive selection in response to heat stress may have also been influenced by historical temperature fluctuations, as suggested by their association with loci identified during Acroporid speciation. These loci under codon-level positive selection during speciation highlight the potential role of genetic diversity in shaping adaptation to environmental changes over evolutionary timescales. Conclusion These findings underscore the significance of genetic diversity in coral reproduction for maintaining reef ecosystems. They also indicate that even minor heat stress can exert significant selective pressure, potentially leading to profound implications for coral reef ecosystems. This research is crucial for understanding the impact of rising seawater temperatures on coral reefs.